Emotion recognition and typographic expression in AI media art: A study on sign - Kim, Young Ho (Edelweiss Applied Science and Technology, 2025)
This study investigates the integration of artificial intelligence (AI) into art, focusing on its influence on emotional expression and human-AI interaction through the interactive artwork, Sign. Utilizing real-time emotion recognition and font psychology, Sign captures participants’ facial expressions, analyzes their emotional states, and visually reflects these through dynamic font transformations. By blending technology with creativity, the artwork offers a novel medium for participants to engage with their emotions while highlighting AI’s role in expanding artistic expression. This study underscores the innovative potential of AI-art collaborations to reshape emotional communication. Despite challenges such as the cultural variability of emotion representation, the findings present pathways for integrating AI to enhance human-AI interactions and emotional experiences in artistic contexts.